A mixed method media analysis of the representation of the South African National Health Insurance Policy in the mainstream media from 2011 to 2019 - Bust, Lynn Hazel (Department of Public Health and Family Medicine, 2022)
Media is a crucial factor in shaping public opinion and setting policy agendas. There is limited research on the role of media in health policy processes in low- and middle-income countries. This study profiles South Africa as a case example, currently in the process of implementing a major health policy reform, National Health Insurance (NHI). A descriptive, mixed methods study was conducted in five phases. Evidence was gathered through a scoping review of secondary literature; discourse analysis of global policy documents on universal health coverage and South African NHI policy documents; and a content and discourse analysis of South African print and online media texts focused on NHI. Representations in the media were analysed and dominant discourses that might influence the policy process were identified. Dominant discourses in SA media were identified relating to ‘health as a global public good', biopolitics, and corruption. Media representations focused on political contestation and the impact of NHI on elite actors. Representations in the media did not acknowledge the lived reality of most of the South African population. The discourses identified might influence the policy process by reinforcing socially dominant discourses and power structures, and hindering public participation. This might reinforce current inequalities in the health system, with negative repercussions for access to health care. This study highlights the need to understand mainstream media as part of a people centred health system, particularly in the context of universal health coverage reforms such as NHI. This would require the formation of collaborative and sustainable networks of policy actors, including actors within media, to develop strategies to counter-act harmful representations in the media that might reinforce inequalities and prevent successful implementation of NHI. Strategies should also investigate how to leverage media within health policy processes to decrease inequalities and increase access to health care. Research should be undertaken to explore media in other diverse formats and languages, and in other contexts, particularly low- and middle-income countries, to further understand media's role in health policy processes.